Bovine kidney 3-methylcrotonyl-CoA and propionyl-CoA carboxylases: Each enzyme contains nonidentical subunits - Lau, Edward P. (1979)
3-Methylcrotonyl-CoA carboxylase (MCase; EC 6.4.1.4) and propionyl-CoA carboxylase (PCase; EC 6.4.1.3) have been obtained in highly purified form from bovine kidney mitochondria. Polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate revealed that each enzyme is composed of nonidentical subunits, including a smaller biotin-free subunit (M(r) 62,000 and 58,000 for MCase and PCase, respectively), and a larger biotin-containing subunit (M(r) 80,000 and 74,000 for MCase and PCase, respectively). The possibility that these subunits were derived from a single, larger precursor polypeptide via proteolysis was explored by purification and electrophoresis of each enzyme in the presence of protease inhibitors, but no evidence for proteolysis was obtained. Specific antisera directed towards each enzyme were prepared. The anti-PCase preparation was used to precipitate crossreacting PCase from a pig heart extract. Analysis of the immunoprecipitate obtained revealed a biotin-containing polypeptide (M(r) 78,000) and a biotin-free polypeptide (M(r) 55,000), suggesting that pig heart PCase also contains nonidentical subunits analogous to those seen in the kidney mitochondrial MCase and PCase. A bipartite subunit structure may be a common feature in mammalian MCase and PCase.